Interpretation of Educational Values in Lontara "Latoa" and its Relevance to the Formation of Student Character in Madrasah Aliyah Negeri Bontang (Hermeneutic Analysis) - Darmawati Darmawati (Journal of Social Science, 2023)
This study aims to interpret the educational values in Lontara Latoa and their relevance to the Pancasila Student Profile in shaping the character of students in a State Islamic Senior High School. The data used comprises dialogues within Lontara Latoa containing moral messages. The research results identify educational values such as honesty, intelligence, religiousness, resilience, national spirit, social concern, and love for the homeland within the messages between Kajao Laliddo and Arungmpone. Data collection employed reading, note-taking, and documentation with a hermeneutic approach. This research is descriptive-qualitative, providing a descriptive data explanation regarding the educational values within Lontara Latoa. The findings demonstrate that the dialogues in Lontara Latoa reflect values such as honesty, religiosity, intelligence, national spirit, social concern, and love for the homeland. These values are relevant to the Pancasila Student Profile, particularly in terms of faith, noble behavior, critical thinking, cooperation, global diversity, and creativity. The study suggests the need for further exploration of cultural diversity in Indonesia and in-depth research into educational values within ancient texts such as Lontara Latoa.